Manajemen Fundraising Wakaf Produktif: Perbandingan Wakaf Selangor (PWS) Malaysia dan Badan Wakaf Indonesia - Faradis, Jauhar; Affandi, M. Yazid; Khilmi, Slamet (UIN Sunan Kalijaga, 2015)
This research is motivated by the low public understanding of the productive waqf and magnitude of potential productive waqf. The purpose of this resesarch is to analyze the condition of BWI and PWS. Results showed that the strategy is the collection of productive waqfperformed by BWI and PWS there are two methods namely: the first method of